2016
DOI: 10.1111/add.13462
|View full text |Cite
|
Sign up to set email alerts
|

Buprenorphine compared with methadone to treat pregnant women with opioid use disorder: a systematic review and meta‐analysis of safety in the mother, fetus and child

Abstract: AimsTo assess the safety of buprenorphine compared with methadone to treat pregnant women with opioid use disorder.MethodsWe searched PubMed, Embase and the Cochrane Library from inception to February 2015 for randomized controlled trials (RCT) and observational cohort studies (OBS) that compared buprenorphine with methadone for treating opioid‐dependent pregnant women. Two reviewers assessed independently the titles and abstracts of all search results and full texts of potentially eligible studies reporting o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
162
2
3

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 200 publications
(171 citation statements)
references
References 62 publications
(240 reference statements)
4
162
2
3
Order By: Relevance
“…75,76 Abundant supporting evidence has rendered methadone the most frequently prescribed opioid agonist during pregnancy; however, more recent research suggests that buprenorphine (monoproduct) may be similarly safe and effective for the treatment of opioid use disorder in pregnant women. 75,[77][78][79] We suggest that care providers seek specialist consultation as needed to determine, on a case-by-case basis, the appropriate agent for opioid agonist treatment of a pregnant patient. Withdrawal management is not suggested during pregnancy, primarily because of the high rates of relapse and the adverse outcomes associated with rapid withdrawal and subsequent relapse, such as maternal and fetal distress, fetal death, fetal hypoxia, preterm labour and long-term developmental issues.…”
Section: Pregnant Womenmentioning
confidence: 99%
“…75,76 Abundant supporting evidence has rendered methadone the most frequently prescribed opioid agonist during pregnancy; however, more recent research suggests that buprenorphine (monoproduct) may be similarly safe and effective for the treatment of opioid use disorder in pregnant women. 75,[77][78][79] We suggest that care providers seek specialist consultation as needed to determine, on a case-by-case basis, the appropriate agent for opioid agonist treatment of a pregnant patient. Withdrawal management is not suggested during pregnancy, primarily because of the high rates of relapse and the adverse outcomes associated with rapid withdrawal and subsequent relapse, such as maternal and fetal distress, fetal death, fetal hypoxia, preterm labour and long-term developmental issues.…”
Section: Pregnant Womenmentioning
confidence: 99%
“…(75, 76) Since these studies are limited by small sample size and confounding factors(17, 77) additional well-designed studies are needed. In a meta-analysis of three randomized controlled trials (n = 223) and 15 observational studies (n = 1923) that compared buprenorphine and methadone treatment in pregnancy no difference in the risk of congenital anomalies was identified.…”
Section: Prenatal Carementioning
confidence: 99%
“…Importantly, buprenorphine's ceiling effect decreases the risk of overdose [8,12,13]. Buprenorphine has been associated with improved outcomes in fetal growth, while causing less neonatal abstinence syndrome when compared to methadone [20][21][22][23]. In 2012, a randomized clinical trial, observed better surrogate measures of fetal well-being via non-stress test and biophysical profile post-dosing of buprenorphine versus methadone [24].…”
Section: Buprenorphine Versus Methadone (And Naltrexone) In Pregnancymentioning
confidence: 99%